Influence of gestational weight gain on low birth weight in short-statured South Indian pregnant women. Issue 5 (May 2018) - Shivakumar, Nirupama; Dwarkanath, Pratibha; Bosch, Ronald; Duggan, Christopher; Kurpad, Anura; Thomas, Tinku
Abstract Background/objectives India contributes to one-third of the global burden of low birth weight (LBW) neonates, which is associated with increased risk of mortality and adverse consequences on long-term health. Factors leading to LBW are multidimensional and maternal short stature is an important component with an inter-generational effect. On the contrary gestational weight gain (GWG) shows an independent positive influence on birth weight. The aim of the present study therefore was to determine the influence of GWG on birth weight in short pregnant women. Subjects/methods A prospective observational cohort of 1254 pregnant women was studied. Total, second and third trimester GWG per week were computed. Women were divided into two groups, "short" and "not-short", using a cut off of 152 cm that corresponded to the 25th percentile for height in the cohort. Association of tertiles of GWG with LBW was examined using log binomial regression analysis. Results "Short" women in highest tertile of total GWG had a significantly reduced adjusted relative risk (ARR 0.37, 95% confidence interval 0.16–0.83, P  = 0.016) for LBW, compared to the lowest tertile. However, there was no significant increase in risk for cesarean section (CS) with increasing tertiles of total GWG. Conclusions In women with height <152 cm a significant reduced risk for LBW was observed with the greatest total GWG, without a significant increase in the risk for CS. This suggests that improving GWG in short women may be beneficial for the birth weight of the offspring.